2004
DOI: 10.1523/jneurosci.1978-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Strengthening Mediated by Bone Morphogenetic Protein-Dependent Retrograde Signaling in theDrosophilaCNS

Abstract: Retrograde signaling is an essential component of synaptic development and physiology. Previous studies show that bone morphogenetic protein (BMP)-dependent retrograde signaling is required for the proper development of the neuromuscular junction (NMJ) in Drosophila. These studies, moreover, raised the significant possibility that the development of central motor circuitry might similarly be reliant on such signaling. To test this hypothesis, retrograde signaling between postsynaptic motoneurons and their pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 32 publications
(63 reference statements)
4
53
0
1
Order By: Relevance
“…While the overwhelming evidence indicates that all Wit responses in motoneurons are mediated through Smads, it is also possible that some non-canonical pathways contribute to BMP neuronal signaling (Baines, 2004;Eaton and Davis, 2005;Sun et al, 2007). To the extent that these Smadindependent pathways operate through transcriptional regulation (Lee et al, 2007), their targets would also have been identified in this screen.…”
Section: Cg13565 Encodes a Putative Neuromodulator Regulated By Bmp Smentioning
confidence: 99%
See 2 more Smart Citations
“…While the overwhelming evidence indicates that all Wit responses in motoneurons are mediated through Smads, it is also possible that some non-canonical pathways contribute to BMP neuronal signaling (Baines, 2004;Eaton and Davis, 2005;Sun et al, 2007). To the extent that these Smadindependent pathways operate through transcriptional regulation (Lee et al, 2007), their targets would also have been identified in this screen.…”
Section: Cg13565 Encodes a Putative Neuromodulator Regulated By Bmp Smentioning
confidence: 99%
“…BMP signaling is also required as a permissive signal to allow fast homeostatic presynaptic plasticity in response to decreased postsynaptic responsiveness at the neuromuscular junction (NMJ) synapse (Goold and Davis, 2007). In addition to its functions at the NMJ, BMP signaling is also required for proper specification of some FMRFamidergic neurons (Allan et al, 2003;Marqués et al, 2003), synaptic transmission between interneurons and motoneurons (Baines, 2004), and eclosion behavior, likely through the regulation of genes of the neuroendocrine axis. This retrograde signaling activity of BMPs has also been described in the mammalian nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BMP pathway plays an important role in retrograde signaling at the larval NMJ (for review, see Keshishian and Kim, 2004) and in the Drosophila CNS (Baines, 2004). To evaluate the role of BMP signaling in the increase in neurotransmitter release induced by the absence of dystrophin, we performed electrophysiological recordings at NMJs lacking both dystrophin and wit (Fig.…”
Section: Bmp Signaling At the Nmj Is Required For The Increased Neuromentioning
confidence: 99%
“…TGF-␤ signaling also regulates synaptic transmission and plasticity in multiple circuits in different organisms including glutamergic transmission at the Drosophila neural muscular junction (McCabe et al, 2004), cholinergic transmission between motoneurons and interneurons in the CNS of Drosophila (Baines, 2004), glutamergic transmission between sensory and motor neurons in Aplysia ganglia (Zhang et al, 1997), and modulation of hippocampal network in mammals (Fukushima et al, 2007;Sun et al, 2007;Zheng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%